Influence of Parents Attention, Emotional Intelligence and Learning Motivation to Learning Outcomes - Wahyuni Ambarwati (STKIP Singkawang, 2018)
In general this research is intended to build knowledge about the extent to which the attention of parents, emotional intelligence, motivation to learn effect student learning outcomes. Therefore, the authors make the title of research is